Queensland Alcohol‐related violence and Night‐time Economy Monitoring (QUANTEM): Rationale and overview. (18th May 2021) - Miller, Peter G.; Coomber, Kerri; de Andrade, Dominique; Livingston, Michael; Puljević, Cheneal; Vakidis, Thea; Carah, Nicholas; Taylor, Nicholas; Burn, Michele; Curtis, Ashlee; Chikritzhs, Tanya; Room, Robin; et al.
Abstract: This commentary introduces the special section on the outcomes of the Queensland Alcohol‐related violence and Night‐time Economy Monitoring project and outlines the political and policy context of the interventions put in place under the Queensland government's Tackling Alcohol‐Fuelled Violence strategy. The development of the strategy was informed by alcohol policy initiatives trialled in other major Australian cities over the past two decades. The articles in this special section examine the impact of the Tackling Alcohol‐Fuelled Violence policy stages on alcohol‐related harms and local economies across selected entertainment precincts (Safe Night Precincts). A rich array of data were utilised, including administrative health and justice data, data reflective of nightlife trading (i.e. foot traffic data, ID scanner data and live music performances) and street surveys. Findings have implications for research, policy and practice and demonstrate the need for comprehensive evaluations that can accommodate the complexities of modern alcohol policy in Australia.